Identification of the genes encoding enzymes involved in the synthesis of the biopolymer paramylon from Euglena gracilis - Mackay, Stephen (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Plant Biotechnology))--University of Stellenbosch, 2010.